British enterprise in Nigeria - Cook, Arthur N. (Philadelphia : London., 1943)
The book provides the historical details of British interest in Nigeria, including economic development, amalgamation and unification of the modern Nigeria.
Thesis (Ph. D.)--University of Pennsylvania, 1927.
Published also without thesis note.
Bibliogrsaphy: p. 291-319.
sju 22/01/2019
Loans
Keywords: Nigeria